Two Diterpenoids From Scutellaria orientalis L. subsp. porphyrostegia Edmondson - Karabacak, Cigdem; Tilki, Tahir; Cengiz, Mustafa (Asian Journal of Chemistry, 2010)
In this study, two diterpenoids viz., Ajugarin V and Scutenisin were isolated from the acetone extract of S. orientalis L. subsp. porphyrostegia Edmondson. The structure of these compounds were elucidated. The compounds were 4α,18-epoxy-6α-acetoxy-neoclerod-13-en-15,16-olide and (13R*)-6α,7β-diisobutryloxy-4α,18; 8β,13-diepoxy-19-hydroxyneoclerod- 15,16-olide.